Challenge in Future Ip-Based Voice Communication System for Air Traffic Control - Nurhidayatulloh, Nurhidayatulloh; Hendrawan, Hendrawan (Jurnal Pendidikan Multimedia (Edsence), 2024)
The most important part of the modernization of Air Traffic Management (ATM) is the Voice Switching and Control System (VSCS) based on Circuit Switching (CS) technology. This technology has Quality of Service (QoS) on Bandwidth, Delay, and Jitter, but it is expensive to implement in small and medium airports. The development of Packet Switching (PS) technology with Internet Protocol (IP) is expected to become an alternative to modern and affordable systems such as the IP-based VSCS communication system. This research uses literature study and experimental methods to develop features and components of a portable IP-based VSCS communication system. The measurement results of this prototype have a delay of 100-150 ms, jitter below 50 ms, 0% packet loss, and varying throughput. Thus, the VSCS prototype built has performed according to the standards required by the International Civil Aviation Organization.